Impact of Distance Learning on Early Childhood Development: A Meta-Analysis - Syafii, Ahmad; Purnama, Sigit; Prasetyo, Gatot (MyResearch ID Publishing, 2024)
Purpose – This study evaluates the impact of distance learning on early childhood development through a meta-analysis, focusing on the effect size of various practices, identifying potential publication biases, and conducting subgroup analyses based on electronic devices, intervention duration, and specific skills taught. Methods/Design/Approach – A meta-analysis was conducted on 87 studies published between 2010 and 2021, selected from databases including Science Direct, Scopus, and PubMed. Comprehensive Meta-Analysis 3.0 software was employed for effect size calculations, variance analyses, and subgroup analyses, alongside publication bias tests using Funnel Scatter Plot, Clip and Fill, Rosenthal, and Orwin’s Fail-Safe N methods. Findings – The overall effect size of distance learning on early childhood development was small (0.186) with significant heterogeneity (I² = 87.358%). Subgroup analysis revealed that mobile-based learning had a larger effect size (0.888) compared to desktop-based learning (0.028). The duration of intervention did not significantly affect outcomes, although longer interventions showed slightly better results. Cognitive and language skills benefited most from distance learning, while other skills like self-efficacy and music showed minimal or negative effects. Originality/Value – This study offers a comprehensive analysis of distance learning's effectiveness in early childhood education, addressing gaps in the literature regarding the impact of device types and intervention durations. The findings contribute valuable insights for the development of more effective distance learning platforms for young children. Practical Implications – The findings suggest that mobile-based distance learning is more effective for early childhood education than desktop-based approaches. Educators and policymakers should prioritize mobile-friendly platforms and focus on cognitive and language development for early learners. Further improvements in distance learning strategies are needed, particularly for non-cognitive skills, to enhance early childhood learning outcomes. Keywords Distance learning, early childhood development, meta-analysis, mobile learning, cognitive skills. Paper type Research paper